Estimation of inelastic displacement demands of flexible-based structures on soft soils - Lu, Yang; Hajirasouliha, Iman; Marshall, Alec M. (Inderscience Enterprises, 2016)
This study aims to develop efficient tools for performance-based seismic design of soil-structure interaction (SSI) systems on soft soils. To simulate the SSI effects, linear and nonlinear 'equivalent fixed-base single-degree-of-freedom' (EFSDOF) oscillators as well as a sway-rocking SSI model were adopted. The nonlinear dynamic response of around 10,000 SSI models and EFSDOF oscillators having a wide range of fundamental periods, target ductility demands, and damping ratios were obtained under a total of 20 seismic records on soft soil sites. Based on the results of this study, a practical method is developed for estimating the base shear and maximum displacement demands of a nonlinear single-degree-of-freedom structure on soft soil deposits. In the proposed procedure, the effect of frequency content of ground motions is considered by normalising the period of vibration by the spectral predominant periods, while the nonlinear EFSDOF models are used to improve the computational efficiency.